Shewanella‐mediated Biosynthesis of Manganese Oxide Micro‐/Nanocubes as Efficient Electrocatalysts for the Oxygen Reduction Reaction. Issue 1 (25th November 2014) - Jiang, Congcong; Guo, Zhaoyan; Zhu, Ying; Liu, Huan; Wan, Meixiang; Jiang, Lei
Abstract Developing efficient electrocatalysts for the oxygen reduction reaction (ORR) is critical for promoting the widespread application of fuel cells and metal–air batteries. Here, we develop a biological low‐cost, ecofriendly method for the synthesis of Mn2O3 micro‐/nanocubes by calcination of MnCO3 precursors in an oxygen atmosphere. Microcubic MnCO3 precursors with an edge length of 2.5 μm were fabricated by dissimilatory metal‐reducing Shewanella loihica PV‐4 in the presence of MnO4− as the sole electron acceptor under anaerobic conditions. After calcining the MnCO3 precursors at 500 and 700 °C, porous Mn2O3‐500 and Mn2O3‐700 also showed microcubic morphology, while their edge lengths decreased to 1.8 μm due to thermal decomposition. Moreover, the surfaces of the Mn2O3 microcubes were covered by granular nanoparticles with average diameters in the range of 18–202 nm, depending on the calcination temperatures. Electrochemical measurements demonstrated that the porous Mn2O3‐500 micro‐/nanocubes exhibit promising catalytic activity towards the ORR in an alkaline medium, which should be due to a synergistic effect of the overlapping molecular orbitals of oxygen/manganese and the hierarchically porous structures that are favorable for oxygen absorption. Moreover, these Mn2O3 micro‐/nanocubes possess better stability than commercial Pt/C catalysts and methanol‐tolerance property in alkaline solution. Thus the Shewanella‐mediated biosynthesis method we provided here might be a new strategy for the preparation of various transition metal oxides as high‐performance ORR electrocatalysts at low cost.